EMPLOYEE ATTITUDE BEFORE AND AFTER WORK RELATIONSHIP POLICY - Kasaya Annisa Rahmaniah; Agus Riyanto; Yudha Heryawan Asnawi (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2020)
The process of work termination of employment is done carelessly, the process is carried out with careful consideration. Termination of employment by PT. This XYZ has an impact on the changing attitudes of its employees. Employee attitude is an important factor in contributing to promotion and high commitment in management practices. Data can be divided into two parts, namely primary data and secondary data. Primary data is a source of data collected by the authors themselves, while secondary data is data collected from other parties. The processing method uses the T test. Termination of employees at PT XYZ provides an increase in employee performance improvement. This can be seen from the faster monthly fulfillment target for employees who are able to innovate and be innovative to work better. PT XYZ's policy must be able to have a positive impact on employees' commitment to remain in the company. The commitment of employees is important for companies in order to maintain assets. This research hopes to be a recommendation for policy makers in the organization. Keywords: Employee, Management, work termination